The cultural politics of U.S. immigration : gender, race, and media - Perry, Leah (Nation of nations (NYU Press), 2016)
"In the 1980s, amid increasing immigration from Latin America, the Caribbean, and Asia, the circle of who was considered American seemed to broaden, reflecting the democratic gains made by racial minorities and women. Although this expanded circle was increasingly visible in the daily lives of Americans through TV shows, films, and popular news media, these gains were circumscribed by the discourse that certain immigrants, for instance single and working mothers, were feared, censured, or welcomed exclusively as laborers. In The Cultural Politics of U.S. Immigration, Leah Perry argues that 1980s immigration discourse in law and popular media was a crucial ingredient in the cohesion of the neoliberal idea of democracy. Blending critical legal analysis with a feminist media studies methodology over a range of sources, including legal documents, congressional debates, and popular media, such as Golden Girls, Who's the Boss?, Scarface, and Mi Vida Loca, Perry shows how even while "multicultural" immigrants were embraced, they were at the same time disciplined through gendered discourses of respectability. Examining the relationship between law and culture, this book weaves questions of legal status and gender into existing discussions about race and ethnicity to revise our understanding of both neoliberalism and immigration."--Publisher's description